RISK MANAGEMENT ANALYSIS ON IMPLEMENTATION OF INFORMATION SYSTEM IN ORGANIZATION LIANTIMOROAN USING COBIT 5 - Ximenes, Abrão (Swiss German University, 2019)
Risk management analysis is to know about the implementation of information system, a part of risk management to be held within the organization to formulate a series of recommendation for the company. In order to get the final result in the form of documentation to support the further development of the system that will be described using COBIT 5 Framework, with the input of information technology processes that are running now. Then it will be obtained the maturity level, after it carry out an analysis of the maturity level has been obtained. The result of the analysis in the form of recommendation, as well as the methods that used to achieve the proposed recommendations.